My Year in Iraq : The Struggle to Build a Future of Hope - Bremer, L. Paul and McConnell, Malcolm (London Simon & Schuster, 2006)
This memoir of fourteen months as America's proconsul in Iraq is the only senior insider's perspective on the crucial period following the collapse of Saddam Hussein's regime. Bremer describes negotiations with emerging Iraqi leaders as they struggle to forge the democratic institutions vital to Iraq's future; his resistance to the cut-and-run policy that would have quickly delivered governance of Iraq to a handful of unrepresentative anti-Saddam exiles; heated sessions among members of America's National Security Council; his frustration with intelligence operations that concentrated on the search for weapons of mass destruction while the insurgency gathered strength; the selfless and courageous work of thousands of American servicemen and -women and civilians; and working with Iraq's traumatized and divided population to find a path to a responsible government.--From publisher description.
Include Index
Keywords: Iraq -- Bremer, L. Paul -- Postwar reconstruction -- Coalition Provisional Authority